2016
DOI: 10.1098/rspb.2016.1632
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic inheritance of parent–offspring cell structure in the clonal diatomCyclotella meneghiniana

Abstract: In cytoplasmic inheritance, structural states of a parent cell could be transmitted to offspring cells via two mechanisms. The first is referred to as the hangover of parent structure, where the structure itself remains and faithfully transmits within offspring cells; the second is structural inheritance, wherein the parent structure functions as a template for development of new offspring structure. We estimated to what extent the parent structure affects the development of offspring structure by structural i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…On the other hand, each chamber included offspring cells from the same founder, which tend to share common fates and cytoplasmic states [28,42]. Also, we found that two sibling cells from the same mother cell had more similar emergence time than cell pairs randomly sampled from the cell population (bootstrap hypothesis test in all pair combinations (S-S, E-E, E-S), p < 0.0001; figure 5).…”
Section: (C) Proximate Factors Influencing Synchronization Of Emergence Timingmentioning
confidence: 76%
“…On the other hand, each chamber included offspring cells from the same founder, which tend to share common fates and cytoplasmic states [28,42]. Also, we found that two sibling cells from the same mother cell had more similar emergence time than cell pairs randomly sampled from the cell population (bootstrap hypothesis test in all pair combinations (S-S, E-E, E-S), p < 0.0001; figure 5).…”
Section: (C) Proximate Factors Influencing Synchronization Of Emergence Timingmentioning
confidence: 76%
“…Cytoplasmic inheritance is non-genetic inheritance in which there is a division of cell states between cell lineages (Shirokawa and Shimada 2016…”
Section: Diatom Morphogenesis: Cytoplasmic Inheritance and Phenotypicmentioning
confidence: 99%
“…Daughter cell microscale surface structure patterns (i.e., morphological characters such as central fultoportulae, striae, central area, and cell diameter) correlate with parental organelles(Shirokawa and Shimada 2016).Cell structure traits are quantitatively different from structural traits inherited by genetic or non-genetic factors. In diatoms, cell structure variation results from the new formation of daughter cells within the parent as incomplete inheritance(Shirokawa and Shimada 2016).Microscale structural patterns on the daughter cell valve reflect not only the environmental conditions the parent cell was subjected to, but also the location of organelles within the parental cell(Shirokawa and Shimada 2016). As a result, diatoms exhibit phenotypic plasticity, and structural variation in shape and pattern of a cell are reflected during size diminution during the diatom life cycle.…”
mentioning
confidence: 99%
See 2 more Smart Citations